NEUROLINGUISTIC APPROACH TO TEACHING ENGLISH AS A FOREIGN LANGUAGE - Potylitsyna, О.; Trichik, М. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
Relevance. Kazakhstan is implementing a complex of updates in education. In this context the system of education is tasked with mastering modern teaching methods and approaches, improving the level of teaching, modernizing public consciousness, developing functional literacy, and trilingualism. The neurolinguistic approach is an innovative way to teach a foreign language. Goal. The following article is aimed to investigate the distinctive features of the neurolinguistic approach and examine the possible activities that can be used for the implementation of the neurolinguistic approach in the classroom of secondary school for teaching English as a foreign language.
Keywords: neurolinguistic approach; activities; foreign language; teaching; school